The Effect of Biofertilization on Plant Growth and its Role in Reducing Soil Pollution Problems with Chemical Fertilizers - Nuri Salem Alnaass; Hossean Khalifa Agil; Najat Alarbi Alyaseer; Mabruka Abubaira; Hamza Khalifa Ibrahim (African Journal of Advanced Pure and Applied Sciences, 2023)
Agriculture, the backbone of global food production, faces the twin challenges of feeding a growing population while protecting soil health and environmental integrity. This summary looks at the emerging field of biofertilization, an eco-friendly alternative that not only improves plant growth but also alleviates soil problems caused by the heavy use of chemical fertilizers. We study the diverse agricultural landscape and analyze the negative impacts of chemical fertilizers on nutrient balance, soil degradation and environmental sustainability. The bright spot lies in biofertilization, an innovative approach that harnesses the power of beneficial microorganisms and organic matter. Through an extensive literature review and empirical analysis, this research sheds light on biofertilization’s remarkable ability to rebalance nutrients, improve soil health, and mitigate the environmental impacts of conventional fertilization practices. Our results underscore the critical role of biofertilization in promoting sustainable agriculture by providing a viable route to increase food production while protecting soil integrity and ecosystem health. In this summary, he advocates the widespread adoption of biofertilization as a transformative practice that contributes to a more food-secure and environmentally sustainable future